As Mulheres na escolarização da educação física no Espírito Santo : $b professoras e autoras (1931-1936) - Bruschi, Marcela (2015)
This paper seeks to understand the participation of 23 teachers majored in Physical Education Course of Espirito Santo, in the 1930s, in schooling of the discipline. It aims to analyze how they perceive their presence as teachers and authors of Physical Education in Espirito Santo. As a theoretical reference, it uses the concepts of fights of representations (CHARTIER, 1990), strategy and tactics (CERTEAU, 1994) and the evidential paradigm (GINZBURG, 1999). Methodologically, it uses of the documental criticism (BLOCH, 2001). As sources, it mobilizes documents of the Escola Normal, of Colégio Nossa Senhora Auxiliadora, of the Permanent Archive of the Center of Physical Education and Sports of the Federal University of Espirito Santo (Cefd/Ufes) (1931-1961), Public Archives of Espirito Santo state, the Revista de Educação (1934-1937), the Diário da Manhã (1908-1937) and the magazine Vida Capichaba (1923-1959). The Physical Education Course was created in 1931 and held by military personel majored at the Military Centre of Physical Education. Although the historiography points out the course as a space of diffusion of an alleged militarization and sportivization of Physical Education, the findings indicate other purposes. Monographs produced by the first teachers, mostly women, majored in the course, identify these other intentions. It was possible to identify the appropriation and the uses of culture in circulation by the students to build their term papers, published in local periodicals. After publications, women have gained prominence and have begun to occupy places in important educational institutions in the region. To give visibility to the work of the 23 teachers of Physical Education, it becomes possible to see how they made use of an accumulated symbolic capital throughout their careers as teachers, as authors, and finally as women who moved in a tactic way in the middle of the speeches, that tried to determine their social roles.